Evaluasi Stabilitas Sediaan Krim Ekstrak Etanol Daun Afrika (Vernonia amygdalina Delile) dengan Basis Vanishing Cream (VC) - Maria T. Nainggolan; Eva S. Simaremare; Rani D. Pratiwi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
Daun afrika (Vernonia amygdalina) contains flavonoids, tannins, saponins, and terpenoids that can be used for pharmacology activity: annihilate the parasites that causing schistosomiasis, malaria leishmaniasis, antiamoeba, antitumor and antimicrobials. The purposes of this research were to screen the phytochemistry of african leaf, formulate and test the stability of vanishing cream (VC) base. The methods used were sample collection, extract preparation, formulation, and stability evaluation. The results showed that extract afrika leaves had alkaloids, flavonoids, tannins, saponins, steroids, and triterpenoids. Extract of daun afrika can be made to good VC base formula including organoleptic test, homogeneity test, pH test, spreading test, sticky test, and VC safety test by distributing questionnaires. The cream was stabil for 21 days at room temperature. Observation of physical properties good performed every week to organoleptis, pH, adhesion, and spreading power. Key words: stability, V. amygdalina, kill parasites, Vanishing Cream